Accessing the Role of Artificial Intelligence in Information Security Risk Management - Baig, Ashiq (2024)
This thesis looks at how Artificial Intelligence (AI), especially large language models (LLMs) like GPT and RoBERTa, can help improve cybersecurity by detecting threats and managing risks. Examples of these cyber threats include phishing and malware. Traditional systems that rely on fixed rules often don’t work well enough.